Analisis Infrastruktur Teknologi Informasi untuk Mendukung Kelangsungan Bisnis pada Platform E-Commerce - Firdaus, Rahmad; Zidan, Abiyyu Al Thoriq; Rajaguguk, Rifaldi Febriansyah; Suwanto, Fredy; Yeremia, Deryl Andeya; Pratama, Dicky (Universitas Methodist Indonesia, 2025)
This research analyzes the implementation of information technology infrastructure in supporting business continuity of e-commerce platforms, focusing on risk management, security, and performance optimization aspects. Using a qualitative methodology with a case study approach, this research integrates COBIT and ITIL frameworks to evaluate IT infrastructure management effectiveness. The results show that the e-commerce platform has achieved 99.95% availability with an average response time of 180ms for standard transactions. The implementation of hybrid cloud-based microservices architecture provides optimal flexibility and scalability in handling demand fluctuations up to 400% from baseline load. Security analysis reveals the effectiveness of zero-trust architecture implementation with a threat detection rate of 98.5%. The integration of COBIT and ITIL frameworks resulted in a 47% increase in IT governance effectiveness, with the DSS domain achieving the highest maturity score of 4.5. This research recommends strategic development including migration to cloud-native architecture, implementation of AI/ML for resource optimization, and strengthening security capabilities through advanced threat detection.